Synergy of Indigenous Law in the Actualization of Local Wisdom-Based Education for Indigenous Fishermen of the Pantura Community as an Effort to Develop Comprehensive and Quality Education - Rohmat, Rohmat (Universitas Negeri Semarang, 2018)
Asemdoyong Village has unique characteristics, but education issues are the main problem in this village. Education, especially in the north coast community area (Pantura) is often not a top priority. This paper explores the potential for the synergy of customary law in enhancing the development of a comprehensive education based on local wisdom in Asemdoyong Village. How customary law is able to function optimally in improving education for rural communities is one of the focuses of this paper.